Western Hudson Bay pedigree (TXT) - Malenfant, René; Davis, Corey; Richardson, Evan; Lunn, Nicholas; Coltman, David (Dryad Digital Repository, 2018)
Tab-delimited text file formatted for use in R (i.e., unknown parents are indicated with NA.) For use in ASReml, the data should be reformatted as columns id, sire, dam with "0" used to indicate unknown parents. For details of the pedigree, see doi: 10.1007/s00300-015-1871-0